Comparison of right hemicolectomies with and without complete mesocolic excision (CME). (1st June 2022) - Cathomas, M; Galli, R; Heigl, A; Lamm, S; Glaser, C; Cathomas, G; Rosenberg, R
Abstract: Objective: Since the concept of complete mesocolic excision (CME) in right hemicolectomies was introduced, it is still under debate if all patients require this radical technique. Methods: Patients with adenocarcinoma of the colon undergoing right hemicolectomies at our hospital were retrospectively analyzed and stratified in a non-CME group (08/2014-04/2018) and a CME group (05/2018-11/2021). Patients were compared in regard to clinical, histopathological and prognostic parameters. CME were classified according to Benz et al. Results: A total of 130 right hemicolectomies were performed, 33 (25.4%) patients were excluded due to other pathologies or emergency patients. Finally, 97 patients were included (53 in the CME group, 39 in the non-CME group). No difference in patient's characteristics were found except more male patients in the CME group (20 vs. 6; p=0.02). Tumors in the CME group were mainly located in the colon ascendens (66.0%), in the non-CME group in the coecum (48.7%; n.s.). In the CME group, 26 of 53 (49.1%) patients were operated laparoscopically compared to 10 of 39 (25.6%) patients in the non-CME group. Da Vinci system were used exclusively in the CME group (5 of 53 (9.4%); p=0.003). TNM classification, histology and UICC stadium showed no significant difference. In total, 50 (94.3%) surgical specimen were classification either as CME 0 or 1. In average, 35.2 lymph nodes (8.2% positive) were found in the CME group compared to 32.7 (16.2% positive) lymph nodes in the non-CME group (p=0.9). No relevant intraoperative complications occurred in both groups. Distance of the mesocolon were available in 39 (73.6%) patients in the CME group and 34 (37.1%) in the non-CME group; the distance tended to be longer in the CME group (mean 116.0 mm in CME group vs. 96.6 mm in non-CME group; p=0.09). Follow-up were 336.4 days in CME-group and 1210.4 days in the non-CME group. In the follow-up, 2 (5.1%) patients in the non-CME group developed a local recurrence in the smaller pelvis. No local recurrence occurred in the CME group (p=0.18). Distant metastasis occurred in 5 of 53 (9.4%) patients in the CME group and in 2 of 39 (5.4%) patients in the non-CME group (p=0.7). Conclusion: This study shows that the benefit for CME in all performed right hemicolectomies is marginal and that the surgical standards was already high in the pre-CME era.